Development of newer adsorbents: activated carbons derived from carbonized cassia fistula - Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Salvi, Monal S.; Jain, Saijal; Hadawale, Snehal D.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia fistula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms of the derived adsorbents produced by thermal and chemical activation was examined for two representative cases, desulfurization of transportation fuels and wastewater treatment. The adsorbents were characterized by FTIR, XRD, XPS, and SEM techniques that indicate specific characteristics useful as an adsorbent. A successful application in the real industrial wastewater treatment and comparison with well recognized commercial adsorbents clearly highlights the utility of the developed newer adsorbents in separation science and technology.

Differentiating process performance of various coagulants in removal of congo red and orange G dyes - Prajapati, Kavita; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Killedar, D. J.; Ranade, Vivek V. (International Journal of Chemical Reactor Engineering, 2016)
Two refractory azo dyes-Congo red and Orange G, especially at high concentrations were subjected to coagulation with different conventional coagulants and newer formulations developed from Aluminum sulfate, Iron (III) chloride, Aluminium chloride, Poly diallydimethylammonium chloride (Poly DADMAC) and Poly Aluminium Chloride (PAC). The highest COD reduction of 99 % was obtained with PAC SAB 18 (Powder Grade PAC) for Congo red at pH 4.5 while the color removal of 99 % was achieved with almost all the coagulants in the present study at specific pH within 3-8. The optimum dose for the iron-based coagulant is 200 mg/L while that of aluminum-based coagulants and PAC is 150-200 mg/L. Results showed that Orange G was more difficult to remove with a maximum COD removal of 65 % and 35 % color removal using various formulations. The combinational formulations of inorganic-inorganic and inorganic- organic produced a substantial enhancement in COD and color removal and reduced sludge. PAC-Fe30/70 produces the minimum sludge of 50 mL/g on Congo red. pH in the range 3-9 showed high reductions in COD and color (90-99 %) for Congo red while jerky rise in COD and color reduction was observed in the case of Orange G after pH 9. An attempt to understand the dye coagulation mechanism has been made based on the specific difference in dye structure and cation speciation.
Keywords: coagulation; Congo red; dye removal; Orange G; Wastewater treatment

Green approach to dye wastewater treatment using biocoagulants - Chethana, M.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Raja, S.; Ranade, Vivek V. (ACS Sustainable Chemistry & Engineering, 2016)
The present study focuses on newer biocoagulants, bioformulations, and the understanding of coagulant behavior with biocoagulants in relation to chemical coagulants. Newer biocoagulants, seeds of Azadirachta indica (AI) and pads of Acanthocereus tetragonus, are discussed along with two known biocoagulants, Moringa oleifera and Cicer arietinum seeds. Dye removal studies were carried out using widely reported Congo red dye to facilitate easy comparison with other conventional coagulants and the effect of various parameters such as initial dye concentration, pH, coagulant dose, etc. are discussed in detail. The use of biocoagulant was found to be highly effective, and up to 99% dye removal was achieved for coagulant doses in the range of 300-1500 mg/L. It was also observed that coagulation is pH sensitive, similar to chemical coagulants. Although the biocoagulant dose is relatively higher than the conventional chemical coagulants, a good value for the sludge volume index, similar to 50 mL/g for 1 h and 30 min, respectively, was obtained for the two coagulants, Acanthocereus tetragonus and Moringa oleifera. A very high particle count compared to chemical coagulants was observed using a focused beam reflectance measurement. Bioformulation with chemical coagulants such as alum, ferric, and aluminum based coagulants can, not only lower doses of biocoagulants (up to one-third) but can also result in significant improvement in the coagulation performance, up to 50% or more.
Keywords: coagulation; dye removal; Effluent treatment; flocculation; pollution

Industrial wastewater treatment for fertilizer industry a case study - Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Desalination and Water Treatment, 2016)
Wastewaters from chemical fertilizer industry mainly contain organics, alcohols, ammonia, nitrates, phosphorous, heavy metals such as cadmium and suspended solids. The nature of effluent streams varies in terms of its constituents and complexity. The present work attempts to fill the void in the literature that mostly reports synthetic wastewater treatment studies, by evaluating effluent treatment solutions and comparison of different methods for real wastewaters from the fertilizer industry. An attempt has been made to devise suitable methodology mainly using a new device in the form of vortex diode for hydrodynamic cavitation and also using adsorption, for several real wastewater streams from different locations in one major fertilizer industry of Maharashtra, India. The strategy involved characterization of wastewaters, studies on the effective removal of chemical oxygen demand (COD) and devising solutions for effective reduction in ammoniacal nitrogena more serious issue in the fertilizer industry. The characterization of wastewaters from different streams revealed huge variation in COD from 50 to 140,000ppm and ammoniacal nitrogen from 6 to 1,700ppm. Some effluent streams contained alcohol up to 5%. Hydrodynamic cavitation using vortex diode and adsorption with modified carbons were used to treat these streams. Cavitation studies were carried out on a pilot plant and the effect of pressure drop, cavitating device and process intensification were studied. It was observed that the effluent treatment strategy requires careful identification and application of suitable treatment method on the basis of the nature of the effluent. Also, hydrodynamic cavitation, using vortex diode appears to be techno-economically attractive option in treating fertilizer wastewaters giving a very high reduction in COD and ammoniacal nitrogen (up to 85%), similar to adsorption. The results clearly identify potential of newer methodologies in the treatment of effluents in the fertilizer industry.

Non-catalytic deep desulphurization process using hydrodynamic cavitation - Suryawanshi, Nalinee B.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Scientific Reports, 2016)
A novel approach is developed for desulphurization of fuels or organics without use of catalyst. In this process, organic and aqueous phases are mixed in a predefined manner under ambient conditions and passed through a cavitating device. Vapor cavities formed in the cavitating device are then collapsed which generate (in-situ) oxidizing species which react with the sulphur moiety resulting in the removal of sulphur from the organic phase. In this work, vortex diode was used as a cavitating device. Three organic solvents (n-octane, toluene and n-octanol) containing known amount of a model sulphur compound (thiophene) up to initial concentrations of 500 ppm were used to verify the proposed method. A very high removal of sulphur content to the extent of 100% was demonstrated. The nature of organic phase and the ratio of aqueous to organic phase were found to be the most important process parameters. The results were also verified and substantiated using commercial diesel as a solvent. The developed process has great potential for deep of various organics, in general, and for transportation fuels, in particular.

Exploiting functionalities of biomass in nanocomposite development: application in dye removal and disinfection along with process intensification - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Sorokhaibam, Laxmi Gayatri; Bhattacharyya, Arnab S. (Clean Technologies and Environmental Policy, 2018)
A green synthesis of multifunctional superparamagnetic nanocomposites using the whole unripened fruit of Cassia fistula (Golden shower) with potential for removal of both cationic and anionic dyes and antimicrobial property is reported for the first time in the present work. A natural medium in the form of clarified butter was used to enhance the multifunctional character. The surface morphology, textural characteristics and composition of the prepared nanoparticles and composites were studied to understand the multifunctional nature. The dye removal was investigated for four different dyes, namely methyl blue, Congo red, rhodamine-B and auramine. Iron nanoparticles were largely effective in the removal of acidic dyes, while the magnetic nanocomposites were effective for the removal of both acidic and basic dyes which can be attributed to the functionalities imparted from Cassia fistula and clarified butter. The dye removal behavior can be significantly enhanced (similar to 50%) using process intensification-adsorption coupled with acoustic cavitation, which also indicated a reduced adsorbent loading as compared to the conventional adsorptive dye removal. The nanomaterials were completely separated from dye solution with absolute ease of separation by applying simple magnetic field. Also, the developed materials were useful in disinfection of E. coli with a high efficiency of 90% confirming significant antimicrobial property at lower concentrations.

Multifunctional activated carbon with antimicrobial property derived from Delonix regia biomaterial for treatment of wastewater - Louis, Mary R.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Bundale, Sunita (Journal of Environmental Chemical Engineering, 2018)
In this work, we report the development of a multifunctional high surface area activated carbon (DRP), from a biomaterial, Delonix regia, with antimicrobial potential and demonstrated its applicability towards removal of two reactive dyes, Reactive Red (RR-120) and Reactive Blue (RB-4) with an adsorption capacity of ∼6.36 and 24 mg·g−1 respectively. The newer multifunctional activated carbon was prepared from the deseeded pods of Delonix regia through thermo-chemical surface modification and characterized for surface and morphological characteristics, chemical composition, and thermal stability. DRP exhibited a high surface area of 1577 m2·g−1 with various active functional groups. The decolourisation efficiency achieved was very high, ∼98% for both the dyes. The effects of various operating parameters like pH, initial dye concentration, adsorbent dosage, surfactant, salt etc. were investigated and the batch adsorption equilibrium data in each dye system was analyzed with various isotherms-Langmuir, Freundlich, and Tempkin. The kinetics of the adsorption process was best represented by pseudo-second order kinetic model and the adsorption efficiency was also illustrated in the binary system of varying dye compositions. DRP could successfully reduce the microbial growth of Gram positive B. subtilis with a higher zone of inhibition.

Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater